2019
DOI: 10.1080/00480169.2019.1605943
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial isolates, antimicrobial susceptibility and multidrug resistance in cultures from samples collected from beef and pre-production dairy cattle in New Zealand (2003–2016)

Abstract: Supplementary Table 1. Sample sites for the six most common genera of bacterial isolates cultured from beef and pre-production dairy cattle for the period 2004 to 2016. The percentage of total isolates for each genus by sampling site are shown in parentheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Salmonella are prevalent in domestic animals such as poultry, pigs, and cattle, and can be transmitted through the food chain by the animal-origin food products (6)(7)(8). Slaughter is considered as an important step causing Salmonella contamination in meat products (6,7).…”
mentioning
confidence: 99%
“…Salmonella are prevalent in domestic animals such as poultry, pigs, and cattle, and can be transmitted through the food chain by the animal-origin food products (6)(7)(8). Slaughter is considered as an important step causing Salmonella contamination in meat products (6,7).…”
mentioning
confidence: 99%
“…The distribution of isolates was biased towards bacterial pathogens associated with enteric disease, respiratory disease, meningitis and sudden death [ 15 , 23 , 24 ]. Although the size of the study population was small, the percentage of isolates expressing MDR was generally higher than that recently reported for other farm animal species in New Zealand [ 25 , 26 ]. The limited number of sample submissions from this population is at odds with estimates of antimicrobial sales in the pork industry, indicating that, in common with other industry sectors, factors other than culture and susceptibility results are the main drivers of antimicrobial use in New Zealand [ 4 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 66%
“…A recent report in the New Zealand dairy industry showed that 21% of veterinarians utilise susceptibility testing, but it is unclear if this corresponds with the number of submissions for bacterial culture [ 28 ]. The low level of susceptibility testing is concerning as it further emphasises a disparity between susceptibility-guided prudent antimicrobial use in the livestock industries in New Zealand and annual antimicrobials sales [ 4 , 25 , 27 ]. Evidence for New Zealand livestock veterinarians is scant, but a recent survey found that 80% of dairy veterinarians prescribe antimicrobials based on a diagnosis, and 65% as a test for response to therapy, in lieu of bacterial culture and antimicrobial susceptibility testing [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited use of bacterial culture and sensitivity testing by veterinarians are other causes of the persistence of the multidrug resistance (MDR) isolates in dairy farms. The findings of the last decades highlight the necessity of using antimicrobial susceptibility testing each time before prescribing an antibiotic [32].…”
Section: Animal Biosecurity 41 Live Animal Managementmentioning
confidence: 99%